a) Ta có: -\(x^2\)+4x - 9
<=> - ( \(x^2\)- 4x + 4 ) - 5
<=> - ( x - 2 )\(^2\) - 5
Vì - ( x - 2 )\(^2\)\(\le\)0 <=> - ( x - 2 )\(^2\) - 5 \(\le\)-5 với mọi x
b) Ta có x\(^2\)- 2x + 9
<=> ( x\(^2\) - 2x +1 ) + 8
<=> ( x - 1 ) \(^2\)+ 8
Vì ( x - 1 ) \(^2\)\(\ge\) 0 <=> ( x - 1 ) \(^2\)+ 8 \(\ge\) 8 với mọi thực x
a,Ta có:\(-x^2+4x-9\)
\(\Leftrightarrow-\left(x^2-4x+4\right)-5\)
\(\Leftrightarrow-\left(x-2\right)^2-5\)
Vì \(-\left(x-2\right)^2\le0\Leftrightarrow-\left(x-2\right)^2-5\le-5\forall x\)
b.Ta có:\(x^2-2x+9\)
\(\Leftrightarrow\left(x^2-2x+1\right)+8\)
\(\Leftrightarrow\left(x-1\right)^2+8\)
Vì \(\left(x-1\right)^2\ge0\Leftrightarrow\left(x-1\right)^2+8\ge8\forall x\)
Bài làm
a) Ta có: -x2 + 4x - 9 < -5
<=> -x2 + 4x - 9 + 5 < 0
<=> -x2 + 4x - 4 < 0
<=> -( x2 - 4x + 4 ) < 0
<=> -( x - 2 )2 < 0
<=> ( x - 2 )2 > 0 ( luôn đúng với mọi x )
Vậy -x2 + 4x - 9 < -5 với mọi x
b) x2 - 2x + 9 > 8
<=> x2 - 2x + 1 > 0
<=> ( x - 1 )2 > 0 ( luôn đúng với mọi x )
Mà với mọi x thì x thuộc tập hợp số thực.
Vậy x2 - 2x + 9 > 8 với mọi x là số thực.